Does Blended Learning Improve Studentâ€™s Learning Independence during the Covid-19 Pandemic? Evidence from a Labuhanbatu University, North Sumatera - Riwayani, Shopia; Harahap, Risma Delima (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
The aim of this study is to analyze the effectiveness of blended learning strategy in increasing the students' learning independence at Labuhanbatu University in North Sumatra. The descriptive method with a quantitative approach was applied in the investigation. The research sample consisted of 92 respondents from Biology Education Study Program of Labuhanbatu University. A questionnaire in the form of statements and a Likert scale were used to collect data. Technique for data analysis was based on percentages. The results of this study revealed that applying blended learning increases, among other elements, learning independence:Â  1) independent of other 76.20%, 2) self-confidence 79.29%, 3) disciplined behavior 83.04%, 4) a sense of responsibility 79.89%, 5) individual initiative attitude 86.63%, 6) self-control 80.46%. Based on these results, blended learning is proven to be an effective learning model that can be applied to increase student learning independence.